ОПЫТ ВНЕДРЕНИЯ СИСТЕМЫ ИНФЕКЦИОННОГО КОНТРОЛЯ В КЛИНИКЕ ФГБОУ ВО СПБГПМУ МИНЗДРАВА РОССИИ - Набиева, Анна Сергеевна; Пузырев, Виктор Геннадьевич; Сорока, Ольга Геннадьевна; Конева, Варвара Олеговна (Медицина: теория и практика, 2020)